A systematic review of peer mentoring interventions for people with traumatic brain injury - Morris, Richard; Fletcher-Smith, Joanna C.; Radford, Kathryn (SAGE Publications, 2016)
Objective: This systematic review sought evidence concerning the effectiveness of peer mentoring for people with traumatic brain injury. Data sources: Fourteen electronic databases were searched, including PsycINFO, MEDLINE, CINAHL, EMBASE and the Cochrane Library, from inception to September 21 2016. Ten grey literature databases, PROSPERO, two trials registers, reference lists and author citations were also searched. Review methods: Studies which employed a model of one-to-one peer mentoring between traumatic brain injury survivors were included. Two reviewers independently screened all titles and abstracts before screening full texts of shortlisted studies. A third reviewer resolved disagreements. Two reviewers independently extracted data and assessed studies for quality and risk of bias. Results: The search returned 753 records, including one identified through hand searching. 495 records remained after removal of duplicates and 459 were excluded after screening. Full texts were assessed for the remaining 36 studies and six met the inclusion criteria. All were conducted in the United States between 1996 and 2012 and employed a variety of designs including two randomised controlled trials. A total of 288 people with traumatic brain injury participated in the studies. No significant improvements in social activity level or social network size were found, but significant improvements were shown in areas including behavioural control, mood, coping and quality of life. Conclusion: There is limited evidence for the effectiveness of peer mentoring after traumatic brain injury. The available evidence comes from small-scale studies, of variable quality, without detailed information on the content of sessions or the ‘active ingredient’ of the interventions.